In vitro Characterization of Biofilm Formation in Prevotella Species - Albaghdadi, Shurooq Zakariya; Altaher, Jenan Bader; Drobiova, Hana; Bhardwaj, Radhika G.; Karched, Maribasappa (Frontiers in Oral Health, 2021)
Background: Periodontitis, a chronic inflammatory oral infection is the outcome of disturbances in the homeostasis of the oral biofilm microbiota. A number of studies have found the occurrence of Prevotella species in elevated levels in periodontitis compared to healthy subjects. Even though different aspects of Prevotella as part of oral biofilm have been studied, in vitro biofilms formed by these species have not been characterized systematically. The objective of this study was to characterize biofilms formed by several Prevotella species and further to assess biofilm inhibition and detachment of preformed biofilms. Methods: Biofilms were grown in 24-well plates containing brucella broth in anaerobic conditions for 3 days, and were quantified using crystal violet staining. Images of SYTO 9 Green fluorescent stained biofilms were captured using confocal microscopy. Biofilm inhibition and detachment by proteinase and DNase I was tested. The biochemical characterization included quantification of proteins and DNA in the biofilms and biofilm-supernatants. Results: P. loescheii, P. oralis and P. nigrescens showed highest biofilm formation. P. nigrescens formed significantly higher amounts of biofilms than P. loescheii (P=0.005) and P. oralis (P=0.0013). Inhibition of biofilm formation was significant only in the case of P. oralis when treated with proteinase (P=0.037), whereas with DNase I treatment, the inhibition was not significant (P=0.531). Overall, proteinase was more effective in biofilm detachment than DNase I. Protein and DNA content were higher in biofilm than the supernatant with the highest amounts found in P. nigrescens biofilm and supernatants. P. oralis biofilms appeared to secrete large amounts of proteins extracellularly into the biofilm-supernatants. Conclusion: Significant differences among Prevotella species to form biofilms may imply their variable abilities to get integrated into oral biofilm communities. Of the species that were able to grow as biofilms, DNase I and proteinase inhibited the biofilm growth or were able to cause biofilm detachment.